Antibacterial Activity of Endophytic Fungi Isolate from Bidara Plant (Ziziphus mauritiana Lam.) Against Bacteria That Cause Digestive Infections by Agar Diffusion Method - Rahmadhani, Paramita; Fitriana, Fitriana; Nurung, Ayyub Harly (Journal Microbiology Science, 2024)
Isolates of endophytic fungi coded IFAZ-6 derived from bidara plants (Ziziphus mauritiana Lam) has antibacterial abilities. This study determine whether those isolates has antibacterial activity against bacteria Escherichia coli. Isolates of endophytic fungi were purified and fermented for 21 days and the fermentation results were extracted using ethyl acetate solvent. The ethyl acetate extract obtained was carried out with a minimum inhibitory concentration (MIC) and a minimum bactericidal concentration (MBC) as well as activity tests with the agar diffusion method. From the test results, statistical tests were carried out, the highest concentration IFAZ-6 isolate extracts that has highest inhibitory zone was 300,000 ppm in E. coli bacteria but only significantly different to 200.000 ppm.